2018
DOI: 10.1021/acs.jpca.8b04589
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Origin of Solvent Induced Enantioselectivity in the Henry Reaction with Cinchona Thiourea as Catalyst

Abstract: In this work, we report an energy decomposition and electronic structure analysis using DFT calculations for the C-C coupling step in the Henry reaction with cinchona thiourea as catalyst and DMF solvent to unravel the origin of enantioselectivity. We found that the conformation of flexible thiourea moiety is affected by the solvent, and in the preferred conformation of thiourea in strong Lewis basic DMF solvent, the N-H sites are in the opposite direction, i.e., in trans conformation. Hence, the thiourea moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In a recent computational study by Baldauf and co-workers, it was predicted that Schreiner’s catalyst (TUR-H; Scheme ) prefers the syn–syn conformation in dichloromethane and switches to the syn–anti conformation upon hydrogen bonding to a ketone substrate. Similarly, the active form of the asymmetrically substituted cinchona thiourea catalyzing the Henry reaction in DMF was found to be the syn–anti rather than the anti–anti conformer . In a comprehensive study of the Cambridge Structural Database, it was found that >98.8% of the 1953 crystal structures of diaryl ureas displayed the anti–anti conformation.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a recent computational study by Baldauf and co-workers, it was predicted that Schreiner’s catalyst (TUR-H; Scheme ) prefers the syn–syn conformation in dichloromethane and switches to the syn–anti conformation upon hydrogen bonding to a ketone substrate. Similarly, the active form of the asymmetrically substituted cinchona thiourea catalyzing the Henry reaction in DMF was found to be the syn–anti rather than the anti–anti conformer . In a comprehensive study of the Cambridge Structural Database, it was found that >98.8% of the 1953 crystal structures of diaryl ureas displayed the anti–anti conformation.…”
Section: Introductionsupporting
confidence: 79%
“…Similarly, the active form of the asymmetrically substituted cinchona thiourea catalyzing the Henry reaction in DMF was found to be the syn−anti rather than the anti−anti conformer. 19 In a comprehensive study of the Cambridge Structural Database, 20 it was found that >98.8% of the 1953 crystal structures of diaryl ureas displayed the anti−anti conformation. The diaryl thiourea structures (190 in total) displayed a broader range of conformers: anti−anti (38%), syn−anti (60%), and syn−syn (2%) conformations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[6a] To explain the enantioselectivity of an asymmetric Henry reaction, Heshmat proposed cinchonathiourea catalyst substrate activation via the syn-anti conformer. [8] Experimental data suggest a similar trend. In an extensive study of crystal structures of urea and thiourea derivatives, Luchini et al [9] showed that around 60% of all thiourea motifs crystallize in a syn-syn or syn-anti fashion.…”
Section: Introductionmentioning
confidence: 79%
“…Consequently, diphenylthiourea populates the syn – anti and syn – syn conformers, thereby lowering its anion binding affinity [6a] . To explain the enantioselectivity of an asymmetric Henry reaction, Heshmat proposed cinchona‐thiourea catalyst substrate activation via the syn – anti conformer [8] . Experimental data suggest a similar trend.…”
Section: Introductionmentioning
confidence: 99%
“…According to this bound state conformational preference, highly differentiated complexation shifts were detected for the two NH protons, that is, very low (0.05–0.09 ppm) for NH(2) and remarkably high (0.59–0.82 ppm) for NH(3) interacting with the enantiomeric substrates (Table S8 in Supporting Information). Even though unexpected, the interaction of thiourea receptors in their syn – anti conformation is already reported in the literature. , …”
Section: Resultsmentioning
confidence: 99%